SISTEM SAPAAN DALAM WAYANG KULIT - Nurhayati, Endang (Diksi, 2008)
This article is about a research study conducted to describe the system,type, and function of form of address in wayang kulit, the Javanese leather-puppetshadow play. The subject under study was a recording of such a play titled KarnaTandhing performed by Timbul Hadiprayitna as the puppet master. The researchmethod applied was descriptive in nature. The research data were obtained bymeans of a listen-and-write technique and analyzed by means of contextualinterpretation.The research results are as follows. 1. The system of form of address inwayang kulit consists of aspects of (1) relation between the addresser andaddressee, (2) sex/gender, (3) setting (place, time, and atmosphere), (4) purpose,(5) honoring, (6) doer, vocation, or profession, (7) marriage and love, (8) mentionof dwelling place, (9) religion and belief, (10) use of pronoun, (11) zero, and (12)mention of specific identity. In type, the form of address can be, among others, (1)a pronoun, (2) a proper name: a pre-adult name, an alternative name, or dasanama,(3) a title attributed due to position of authority, (4) a name others use to call one,(5) a hereditary form of address, (6) paraban "˜a name given due to intimacy', (7)poyokan "˜a derogatory or mocking name', (8) a profession, (9) a doer of an act, (10)an expression of fondness, (11) an expression of being proud of one, (12) anexpression of friendship, (13) an expression of displeasure, annoyance, or anger,(14) an expression in self-introduction, (15) an expression for peprenahan/mbasakke "˜showing how one is related to the other by blood, age, etc.', (16) anexpression related to where one dwells, (17) an expression related to position ofauthority, (18) an expression in honoring, (19) an expression used due to marriage:adult name, husband's name, name of first child, (20) a form of address used whenaddressing a god, goddess, or God, (21) a form of address for the wife of a king,(22) a form of address of zero nature, (23) an expression of cursing, (24) a form ofaddress of specific nature, (25) a noun plus mu, e, or ne, (26) a noun, (27) a nounplus ku, (28) a form of address related to religion, (29) a form of address related tokinship plus e or ne, (30) a form of address used falsely/in playacting/pretence, and(31) a form address to point one out. In function, the form of address can be (1)honorific, i.e., to honor one, (2) to call out to one, (3) to call one with an attribute,(4) mbasakke "˜to show how one is related to the other by blood, age, etc., (5) tomock the other, (6) to show intimacy/to make intimate, (7) to show one's place oforigin, (8) to introduce oneself, (9) to build a certain atmosphere, (10) to besarcastic, (11) to clarify one's identity, (12) to be used falsely in dramatization orin a play or in pretence, and (13) to make a comic effect.Keywords: form of address, wayang kulit, system, type, function